Production of diacylglycerol‐enriched oils by enzymatic interesterification and molecular distillation using soybean oil and distilled saturated monoacylglycerol. Issue 6 (25th January 2017) - Chen, Qiong; Li, Ying; Fu, Junning; Ma, Xiang; Teng, Yinglai; Wang, Yong
Abstract : The blend of refined soybean oil and distilled saturated monoacylglycerol in a mass ratio of 70: 30 w/w were enzymatically interesterified under the optimized enzyme dosage (5% w/w) and time (5 h) at 60°C, followed by further purification through molecular distillation (MD). All samples were evaluated and compared in terms of their iodine value (IV), acylglycerols, fatty acid composition, solid fat content (SFC), crystallization, and melting properties. The diacylglycerol content in the MD residual was found increased from 16.2% in interesterified oils to 22.6%. As the temperature increased, the SFC in the MD residual declined to the similar level of that in RSO. However, the crystallization onset temperature and melting point measured by differential scanning calorimetry were much higher than those of RSO. Moreover, the presence of β′ crystal was found in the MD residual by X‐ray diffraction and polarized light microscopy. In addition, the MD distillate had 27.4% of unsaturated fatty acids and the lowest IV amongst samples. Considering the properties above, the MD residual (diacylglycerol‐enriched oil) could be considered as plastic fats for fluid margarine and the MD distillate (by‐product) with 36.8 g/100 g of IV could be a potential emulsifier for oil and fat products. Practical applications : An innovative design for the production of diacylglycerol‐enriched oils was developed through optimized enzymatic interesterification and MD afterwards using oversupplied DSM and inexpensive RSO in China. On one hand, the resulting MD residual showed its promising application for fluid margarine because of its relatively high value in DAG, unsaturated fatty acid content, crystallization onset temperature, and melting point, as well as the existence of β′ crystal form found inside. On the other hand, the MD distillate as the MD by‐product may become a novel food emulsifier preferred by general consumers due to its lowest IV and enhanced unsaturated fatty acid content. The production of DAG‐enriched oils was developed using refined soybean oil (RSO) and distilled saturated monoacylglycerol (DSM) via coupling of optimized enzymatic interesterification and molecular distillation. The resulting MD residual and distillate were characterized by several physical and chemical analyses (e.g., GC‐FID, DSC, p‐NMR, XRD, and PLM) in order to prove their applicability for oil and fat products, especially in fluid margarine and food emulsification. Abstract : The production of DAG‐enriched oils was developed using refined soybean oil (RSO) and distilled saturated monoacylglycerol (DSM) via coupling of optimized enzymatic interesterification and molecular distillation. The resulting MD residual and distillate were characterized by several physical and chemical analyses (e.g., GC‐FID, DSC, p‐NMR, XRD, and PLM) in order to prove their applicability for oil and fat products, especially in fluid margarine and food emulsification.